Proposed Marketing Strategy for Independent Music Project: A Case Study of Dua Mata Pisau - Atarrahim Iqbal Putra Riyadi (Green Publisher Indonesia, 2025)
Dua Mata Pisau is a new independent music project from Jakarta, Indonesia, currently preparing for its first music release. The rapid growth of the music industry in the digital era presents both opportunities and challenges for independent musicians. Digitalization enables easier distribution of music through digital streaming platforms (DSPs) such as Spotify, Apple Music, and YouTube Music. However, this also increases competition, making it difficult for new musicians to gain visibility and effectively monetize their work. This study aims to assist Dua Mata Pisau in determining an appropriate marketing strategy by exploring audience-based market segmentation, identifying the most attractive target segment, and developing a positioning strategy aligned with its resources and competencies. The research utilized data and insights from key industry stakeholders—such as music producers, artist managers, and label representatives—supported by secondary data, including music consumption trends, streaming platform reports, and industry analyses. Through segmentation analysis, three primary segments were identified: Diehard Fans, Functional Users, and Aspirational Learners. By applying frameworks such as segment attractiveness assessment, market access evaluation, and value proposition analysis, the study concludes that Dua Mata Pisau should adopt a multi-segment targeting strategy. This strategy involves tailored offerings for each segment, leveraging the project's unique resources and capabilities. The strategic implementation culminates in the planned release of Dua Mata Pisau’s debut single in June 2026. The findings provide actionable insights for independent musicians seeking to professionalize their marketing approach while contributing to the academic discourse on strategic marketing in the creative industry.